2013
DOI: 10.1021/nn3049494
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Polyplex- and Lipoplex-Mediated Delivery of Nucleic Acids: Real-Time Visualization of Transient Membrane Destabilization without Endosomal Lysis

Abstract: Lipoplexes and polyplexes are widely applied as nonviral gene delivery carriers. Although their efficiencies of transfection are comparable, their mechanisms of delivery, specifically at the level of nucleic acid release from endosomes, are different. Thus, lipoplex-mediated release is proposed to rely on lipid mixing, as occurs between lipoplex and endosomal target membrane, the ensuing membrane destabilization leading to nucleic acid delivery into the cytosol. By contrast, the mechanism by which polyplexes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
405
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(428 citation statements)
references
References 28 publications
21
405
2
Order By: Relevance
“…On the one hand, DOTAP is a monovalent cationic lipid. Previous reports indicated that the ion‐pair effects led to efficient endosomal escape in lipid‐based formulations 26, 27. In our work, the ion‐pairs might form between the cationic DOTAP and the anionic lipids on the endosome membrane, which can induce the disassembly of LGCP and allow the release of the complex of TAT‐GNs/Cas9 protein/sgPlk1 plasmid from LGCP.…”
Section: Resultsmentioning
confidence: 58%
“…On the one hand, DOTAP is a monovalent cationic lipid. Previous reports indicated that the ion‐pair effects led to efficient endosomal escape in lipid‐based formulations 26, 27. In our work, the ion‐pairs might form between the cationic DOTAP and the anionic lipids on the endosome membrane, which can induce the disassembly of LGCP and allow the release of the complex of TAT‐GNs/Cas9 protein/sgPlk1 plasmid from LGCP.…”
Section: Resultsmentioning
confidence: 58%
“…17,18,21,24 These kinetics and intracellular behaviors are in good agreement with the results using similar carriers. [23][24][25] In our previous study, Py-AA-TO was shown to selectively visualize the siRNA encapsulated in a polymer-based carrier. 11 We thus examined whether the fluorescence signal of Py-AA-TO could be a good indicator to assess not only cellular uptake but also the disassembly of the polyplex.…”
Section: Resultsmentioning
confidence: 98%
“…In that case, fluorescence will only return once the polynucleotides have dissociated from their carrier. This principle was elegantly explored to develop an endosomal escape assay based on the (de)quenching of small oligonucleotide fragments 168 . By simultaneously labeling different types of endosomal vesicles, the specific type of endosomes from which complexes are preferentially released has been recently identified 169 .…”
Section: Lighting Up the Intracellular Delivery Path Of Pdna And Mrnamentioning
confidence: 99%